Comparative assessment of single and joint effects of diuron and Irgarol 1051 on Arctic and temperate microalgae using chlorophyll a fluorescence imaging. (May 2017) - Kottuparambil, Sreejith; Brown, Murray T.; Park, Jihae; Choi, Soyeon; Lee, Hojun; Choi, Han-Gu; Depuydt, Stephen; Han, Taejun
Abstract: Ship groundings and ice-breakers can cause pollution of the polar environment with antifouling biocides such as diuron and Irgarol 1051. The present study used pulse amplitude modulated fluorometry to compare single and joint toxicities of diuron and Irgarol 1051 on two freshwater taxa of microalgae ( Chlorella and Chlamydomonas ) originating from Arctic and temperate regions. 30 min acute toxicity tests using chlorophyll a (Chl a ) fluorescence revealed that Arctic strains of microalgae were more sensitive to herbicides than their temperate counterparts. Diuron and Irgarol 1051 had equal toxicities in the Arctic species, while Irgarol 1051 was more toxic (EC50 = 5.55–14.70 μg L −1 ) than diuron (EC50 = 12.90–>40 μg L −1 ) in the temperate species. Toxicity assessment of various mixtures of diuron and Irgarol 1051 revealed antagonistic, additive, and synergistic effects. Our data suggest that herbicides can adversely affect photosynthesis in Arctic microalgae at relatively low levels, and their impact can increase under complex mixture conditions.